1980
DOI: 10.1071/ar9801147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protected casein supplements on pasture intake, milk yield and composition of cows in early lactation

Abstract: Thirty dairy cows in early lactation were individually fed in stalls on high quality pasture (Lolium peuenne, Dactylis glomerata and Trifoliium repens) and given either formaldehyde-treated casein or untreated casein at 1000 g/day. Nitrogen content and apparent digestibility of herbage nitrogen was 2.8 and 70.4% respectively. Treated casein significantly increased the yield of milk by 13 % and milk protein by 15 % although neither supplement affected milk composition. High-producing cows showed a greater respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 0 publications
2
15
0
1
Order By: Relevance
“…The numerical differences in milk production that we observed did not approach the same level of significance as did the differences in calf gain, although they followed the same general pattern. Increased gain in calves and increased milk production when greater quantities of metabolizable protein were supplied to cows has been observed by other researchers (Rogers et al, 1980;Lee et al, 1985;Blasi et al, 1991). In contrast, Wiley et al (1991) reported no effect on milk production or gain in calves from supplying additional CP from a high-escape source.…”
Section: Discussionsupporting
confidence: 55%
“…The numerical differences in milk production that we observed did not approach the same level of significance as did the differences in calf gain, although they followed the same general pattern. Increased gain in calves and increased milk production when greater quantities of metabolizable protein were supplied to cows has been observed by other researchers (Rogers et al, 1980;Lee et al, 1985;Blasi et al, 1991). In contrast, Wiley et al (1991) reported no effect on milk production or gain in calves from supplying additional CP from a high-escape source.…”
Section: Discussionsupporting
confidence: 55%
“…The pattern of hind weight change in Expt 2 most closely parallels N levels in the selected herbage (Fig. 2) and may indicate a deficiency of essential amino acids for lactating deer, as shown for lactating dairy cattle fed fresh ryegrass-based forages (Rogers et al 1979(Rogers et al , 1980. This needs further investigation.…”
Section: Discussionmentioning
confidence: 53%
“…Offering undegradable protein supplements to cows grazing generous amounts of pasture have usually not increased milk yield (Brookes, 1984;Penno et al, 1995b;Rusdi and Van Houtert, 1997;Stockdale et al, 1997), the opposite being the case when pasture availability was restricted (Rogers et al, 1980;Minson, 1981), as in the current experiments. The total diets of cows offered the MG supplements in the autumn and winter of experiment 2 were likely to have exceeded a CP concentration of 17 g per 100 g DM, which should have been adequate for milk production (National Research Council, 1989).…”
Section: Figurementioning
confidence: 52%